Low-spatter high-brightness water-based flux for photovoltaic module welding and preparation method thereof

CN122895751APending Publication Date: 2026-10-13YUNNAN TIN IND TIN MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611019715.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-09
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

然而,现有水基助焊剂在光伏组件焊接工艺中仍面临一系列技术瓶颈:第一,水基助焊剂以水为主要溶剂,因此在焊接过程中飞溅严重,飞溅的焊料颗粒可能附着在电池片表面,造成外观缺陷、隐裂甚至短路,直接影响组件良率和可靠性

Benefits of technology

(1)低飞溅性:通过酯类助剂与聚乙二醇之间相互作用,再协同高沸点溶剂,增加助焊剂粘度,同时调控蒸发速度,有效抑制焊接过程中的水分爆发性蒸发,降低了水基助焊剂的飞溅。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application provides a low-splashing high-brightness water-based flux for photovoltaic module welding and a preparation method thereof. The flux is composed of the following raw materials in mass percentage: 1-3% of a film forming agent, 2-5% of a composite organic acid active agent, 1-3% of an ester-based auxiliary agent, 0.1-0.5% of a surfactant, 3-8% of a high-boiling-point solvent, 0.1-0.5% of a corrosion inhibitor and 0.3-0.5% of an antioxidant, and the rest is deionized water. The flux realizes the comprehensive performance of low splashing, no irritating smell, less residue and cleaning-free in the welding process, the welding spot is bright and full, the corrosion of the circuit board welding is small, and the requirements of the photovoltaic module solder strip tinning process and the photovoltaic module string welding process can be met simultaneously.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of photovoltaic module welding materials technology, specifically to a low-splatter, high-brightness, low-VOC water-based flux for tinning of photovoltaic module solder strips and string soldering of solar cells, and its preparation method. Background Technology

[0002] Against the backdrop of the continued advancement of dual-carbon policies and the rapid iteration of photovoltaic technology, high efficiency, low degradation, long lifespan, and green manufacturing have become the core development directions for photovoltaic module manufacturing. In the photovoltaic module manufacturing process, flux is an indispensable auxiliary material for ensuring the welding quality of photovoltaic modules. Its main functions are to remove oxides from the surface of the solder and copper strip, reduce the surface tension of the solder, and promote the wetting of the molten solder onto the metal substrate.

[0003] Traditional fluxes used for photovoltaic module welding often employ rosin-based or organic acid-based formulations, with volatile organic solvents such as isopropanol and ethanol as the main carriers, typically containing VOCs exceeding 70%. These fluxes present several drawbacks in the photovoltaic module welding process: firstly, they release large amounts of irritating volatile gases during welding, polluting workshop air quality, endangering the health of operators, and contradicting the increasingly stringent green manufacturing requirements of the photovoltaic industry; secondly, organic solvents are flammable and explosive, posing safety hazards.

[0004] To meet green and environmental protection requirements, water-based fluxes have gradually entered the photovoltaic module welding field in recent years. Water-based fluxes use deionized water as the main solvent, which can significantly reduce VOC emissions. However, existing water-based fluxes still face a series of technical bottlenecks in photovoltaic module welding processes: First, water-based fluxes use water as the main solvent, resulting in severe spattering during welding. Spattered solder particles may adhere to the surface of the solar cells, causing appearance defects, microcracks, or even short circuits, directly affecting module yield and reliability. Second, photovoltaic modules are exposed to outdoor humid and hot environments for extended periods. If the corrosiveness of flux residues is not effectively controlled, it may lead to increased resistance at the solder joints and discoloration of the silver grid lines, thus affecting service life. Third, photovoltaic modules are appearance-sensitive products; the surface condition of the soldered strips directly affects customers' visual evaluation of the module quality. If the flux exhibits darkening, pinholes, or incomplete saturation after welding, it will be difficult to meet the photovoltaic industry's requirement for a bright and full appearance.

[0005] Therefore, developing a water-based flux for welding photovoltaic modules that combines low spatter, non-corrosiveness, high brightness, and environmental friendliness is of great significance for improving the quality and long-term reliability of photovoltaic module products. Summary of the Invention

[0006] The purpose of this invention is to overcome the shortcomings of the prior art and provide a low-splash, high-brightness water-based flux for photovoltaic module welding, which is characterized by low spatter, non-corrosiveness, high gloss, no irritating odor, minimal residue, and no need for cleaning, as well as its preparation method. This flux can simultaneously meet the requirements of both the tinning process for photovoltaic module solder strips and the string soldering process for photovoltaic modules.

[0007] To achieve the above objectives, the present invention provides the following technical solution: A low-splatter, high-brightness water-based flux for welding photovoltaic modules, comprising the following raw materials by weight percentage: Film-forming agent 1-3%, complex organic acid surfactant 2-5%, ester auxiliaries 1-3%, surfactant 0.1-0.5%, high boiling point solvent 3-8%, corrosion inhibitor 0.1-0.5%, antioxidant 0.3-0.5%, and the remaining solvent is deionized water.

[0008] Preferably, the film-forming agent is polyethylene glycol with a molecular weight of 400-6000. In this invention, polyethylene glycol is used as a film-forming agent to form a uniform protective film on the post-weld surface, preventing discoloration and oxidation due to prolonged storage. Simultaneously, the interaction between polyethylene glycol and ester solvents synergistically inhibits explosive evaporation of moisture, which is one of the key factors in achieving low spatter.

[0009] Preferably, the composite organic acid activator is prepared by compounding low-boiling-point organic acids and high-boiling-point organic acids in a mass ratio of 1:0.5 to 1:1.5. The low-boiling-point organic acid is selected from any one of malonic acid, glycolic acid, and succinic acid, and the high-boiling-point organic acid is selected from any one of glutaric acid, itaconic acid, malic acid, and citric acid. The low-boiling-point organic acid begins to decompose and exert its deoxidizing effect at lower temperatures, while the high-boiling-point organic acid can continuously contribute activity in the high-temperature range. The compounding of the two can achieve a stepwise release of activity and maintain stable activity over a wide temperature range.

[0010] Preferably, the ester auxiliaries are selected from one or more of diester esters and polyol esters.

[0011] More preferably, the ester additive is any one or a combination of diethylene glycol diacetate, dimethyl glutarate, dimethyl adipate, polyethylene glycol laurate, propylene glycol methyl ether acetate, and propylene glycol diacetate. In the flux of the present invention, the ester additive has multiple functions: firstly, the inherent properties of the ester additive can reduce the interfacial tension gradient during soldering, promoting the formation of a smooth and bright surface on the solder and significantly improving the brightness of the tin layer; secondly, the ester additive can form a composite solvent system with film-forming agents and high-boiling-point solvents in the flux, which can finely adjust the viscosity of the flux. Simultaneously, the hydrophobic alkyl chains of the ester can be oriented at the gas-liquid interface, forming a dynamic molecular barrier layer. This barrier layer can slow down the diffusion rate of water molecules from the liquid core to the surface, allowing the flux to evaporate slowly during the preheating stage and avoiding splashing caused by explosive boiling of water; thirdly, the selected ester additives have a boiling point lower than the welding temperature (230~300℃), and can be completely decomposed and volatilized during the welding process without any residue, ensuring a clean and bright solder joint surface.

[0012] Preferably, the surfactant is selected from one or more combinations of polyoxyethylene sorbitan monolaurate (Tween-80), fatty alcohol polyoxyethylene ether (AEO-9), isomeric tridecyl alcohol polyoxyethylene ether phosphate (E1310P), alkylphenol polyoxyethylene polyoxypropylene ether (NPE-108), and octylphenol polyoxyethylene ether (OP-10). The surfactant can further reduce the surface tension of the water-based flux and improve its wettability to copper strips and solder.

[0013] Preferably, the high-boiling-point solvent is selected from one or more combinations of tetrahydrofurfuryl alcohol, isopropanol, triethylene glycol butyl ether, dipropylene glycol butyl ether, diethylene glycol butyl ether, dipropylene glycol dimethyl ether, and propylene glycol butyl ether. On the one hand, the high-boiling-point solvent can effectively reduce the evaporation rate of the system during the preheating stage, avoiding splashing caused by the violent evaporation of moisture and low-boiling-point components; on the other hand, the high-boiling-point solvent can evaporate promptly after high-temperature welding, leaving very little residue after welding.

[0014] Preferably, the corrosion inhibitor is one or more combinations of triethanolamine, N,N-methylenebenzenebisbenzoamide, benzotriazole, methylbenzotriazole, 2-ethylimidazole, dimethylethanolamine, and sodium gluconate.

[0015] Preferably, the antioxidant is one or more of hydroquinone, catechol, tea polyphenols, and 2,6-di-tert-butyl-p-cresol.

[0016] The preparation method of the low-spatter, high-brightness water-based flux for photovoltaic module welding according to the present invention includes the following steps: (1) Add deionized water, additives and surfactants to the reaction vessel in sequence, stir evenly to form composite solvent A; (2) Under stirring conditions of 300 to 600 r / min, the high-boiling-point solvent and film-forming agent are added to solvent A, and stirring is continued until the mixture is completely homogeneous to obtain mixture B; (3) Keep stirring, and finally add the compounded organic acid surfactant, corrosion inhibitor and antioxidant to the mixture B, and continue stirring for 20~30 min until the system is completely transparent and uniform; (4) After the obtained solution is allowed to stand, it is filtered through a 0.45-1.0 μm filter membrane to obtain the photovoltaic low-splash high-brightness water-based flux.

[0017] The beneficial effects of this invention are as follows: (1) Low spattering: Through the interaction between ester additives and polyethylene glycol, and in conjunction with high-boiling-point solvents, the viscosity of the flux is increased, while the evaporation rate is controlled, effectively suppressing the explosive evaporation of water during the welding process and reducing the spattering of water-based flux.

[0018] (2) High gloss of solder joints: Under the dual action of ester additives and surfactants, the wettability and spreadability of flux to solder are significantly improved. Its low residue characteristics make the surface of the solder after welding bright and smooth. At the same time, under the action of film-forming agent, the surface after welding can remain bright and colorless for a long time.

[0019] (3) Low residue characteristics: Most of the raw materials used in this invention can be decomposed and volatilized during high-temperature welding. There is no sticky residue on the surface after welding, the board surface has excellent insulation performance, and cleaning is not required after welding, which greatly reduces production energy consumption and cost and improves production efficiency.

[0020] (4) Environmental protection: The main component of this invention is deionized water, with extremely low organic solvent content. There is almost no VOC emission during welding, no irritating odor is generated, and storage and transportation are safe and environmentally friendly. It solves the safety hazards of flammability and explosion of traditional alcohol solvent fluxes and fully complies with environmental directives such as RoHS and REACH.

[0021] In summary, the flux of this invention uses deionized water as the main solvent, making it a water-based flux. It is rosin-free, halogen-free, and contains very little organic solvent. Through the compounding of organic acid activators, the synergistic effect of high-boiling-point solvents and ester solvents, and the addition of corrosion inhibitors and antioxidants, it achieves comprehensive performance characteristics such as low spatter, no corrosion, no irritating odor, minimal residue, and no need for cleaning during the soldering process. The solder joints are bright and full, with minimal corrosion to the circuit board. It can simultaneously meet the requirements of the tinning process for photovoltaic module soldering strips and the string soldering process for photovoltaic modules. It is chemically stable, convenient to store and transport, and has good application prospects. Detailed Implementation

[0022] The present invention will now be described in detail and in complete detail with reference to the embodiments. Example 1

[0023] A low-splatter, high-brightness water-based flux for welding photovoltaic modules, comprising the following components by weight percentage: Polyethylene glycol 400 1% 2% succinic acid Itaconic acid 1% 1% propylene glycol diacetate 1% diethylene glycol diacetate Tween-80 0.5% Dipropylene glycol butyl ether 4% 2% diethylene glycol butyl ether Benzotriazole 0.2% Sodium gluconate 0.2% Hydroquinone 0.3% Deionized water balance.

[0024] The flux is prepared as follows: Deionized water, propylene glycol diacetate, diethylene glycol diacetate, and Tween-80 are added sequentially to a reaction vessel and stirred until homogeneous to form a composite stable solvent; then dipropylene glycol butyl ether, diethylene glycol butyl ether, and polyethylene glycol 400 are added to the composite stable solvent and stirred until completely mixed to obtain a mixed liquid; stirring is maintained, and finally succinic acid, itaconic acid, benzotriazole, sodium gluconate, and hydroquinone are added to the mixed liquid and stirred for 20-30 minutes. After standing and filtering, a white transparent liquid flux is obtained, denoted as S-1. Example 2

[0025] A low-splatter, high-brightness water-based flux for welding photovoltaic modules, comprising the following components by weight percentage: Polyethylene glycol 600 2% 1% malonic acid Glutaric acid 1% Dimethyl glutarate 1.5% AEO-9 0.2% NPE-108 0.2% Tetrahydrofurfuryl alcohol 3% 5% triethylene glycol butyl ether Benzotriazole 0.3% Triethanolamine 0.2% catechol 0.3% Tea polyphenols 0.1% Deionized water balance.

[0026] The flux is prepared as follows: Deionized water, dimethyl glutarate, AEO-9, and NPE-108 are added sequentially to a reaction vessel and stirred until homogeneous to form a composite stable solvent; then tetrahydrofurfuryl alcohol, triethylene glycol butyl ether, and polyethylene glycol 600 are added to the composite stable solvent and stirred until completely mixed to form a mixed liquid; stirring is maintained, and finally malonic acid, glutaric acid, benzotriazole, triethanolamine, catechol, and tea polyphenols are added to the mixed liquid and stirred for 20-30 minutes. After standing and filtering, a white transparent liquid flux is obtained, denoted as S-2. Example 3

[0027] A low-splatter, high-brightness water-based flux for welding photovoltaic modules, comprising the following components by weight percentage: Polyethylene glycol 1000 1.5% Glycolic acid 2% Malic acid 1.5% Dimethyl adipic acid 1.5% E1310P 0.3% 3% Propylene glycol butyl ether 2% dipropylene glycol dimethyl ether Ethylimidazole 0.1% Tea polyphenols 0.2% 2,6-Di-tert-butyl-p-cresol 0.15% Deionized water balance.

[0028] The flux is prepared as follows: Deionized water, dimethyl adipate, and E1310P are added sequentially to a reaction vessel and stirred until homogeneous to form a composite stable solvent; then propylene glycol butyl ether, dipropylene glycol dimethyl ether, and polyethylene glycol 1000 are added to the composite stable solvent and stirred until completely mixed to form a mixed liquid; stirring is maintained, and finally glycolic acid, malic acid, 2-ethylimidazole, tea polyphenols, and 2,6-di-tert-butyl-p-cresol are added to the mixed liquid and stirred for 20-30 minutes. After standing and filtering, a white transparent liquid flux is obtained, denoted as S-3. Example 4

[0029] A low-splatter, high-brightness water-based flux for welding photovoltaic modules, comprising the following components by weight percentage: Polyethylene glycol 600 3% Succinic acid 2.5% 2% citric acid 1% polyethylene glycol laurate OP-10 0.1% AEO-9 0.1% 3% triethylene glycol butyl ether Isopropanol 4% N,N-Methylenebis(phenyl)amide 0.1% Triethanolamine 0.2% Hydroquinone 0.3% Deionized water balance.

[0030] The flux is prepared as follows: Deionized water, polyethylene glycol laurate, OP-10, and AEO-9 are added sequentially to a reaction vessel and stirred until homogeneous to form a composite stable solvent; then triethylene glycol butyl ether, isopropanol, and polyethylene glycol 600 are added to the composite stable solvent and stirred until completely mixed to form a mixed liquid; stirring is maintained, and finally succinic acid, citric acid, N,N-methylenebisphenylamide, triethanolamine, and hydroquinone are added to the mixed liquid and stirred for 20-30 minutes. After standing and filtering, a white transparent liquid flux is obtained, denoted as S-4. Example 5

[0031] A low-splatter, high-brightness water-based flux for welding photovoltaic modules, comprising the following components by weight percentage: Polyethylene glycol 6000 2.5% 2.5% malonic acid Citric acid 2.5% 1% Propylene glycol methyl ether acetate Dimethyl glutarate 2% NPE-108 0.1% Diethylene glycol butyl ether 3% Methylbenzotriazole 0.1% Dimethylethanolamine 0.1% 2,6-Di-tert-butyl-p-cresol 0.5% Deionized water balance.

[0032] The flux is prepared as follows: Deionized water, propylene glycol methyl ether acetate, dimethyl glutarate, and NPE-108 are added sequentially to a reaction vessel and stirred until homogeneous to form a composite stable solvent. Then, diethylene glycol butyl ether and polyethylene glycol 6000 are added to the composite stable solvent and stirred until completely mixed to form a mixed liquid. While stirring, malonic acid, citric acid, methylbenzotriazole, dimethylethanolamine, and 2,6-di-tert-butyl-p-cresol are added to the mixed liquid and stirred for 20-30 minutes. After standing and filtering, a white transparent liquid flux, denoted as S-5, is obtained.

[0033] The fluxes prepared in Examples 1-5 were subjected to simulated performance tests, including the following tests: 1. Dip-coating simulation test: Copper sheets coated with flux were preheated above molten tin at 265℃ for 10 seconds and then immersed in Sn-0.7Cu solder bath at 265℃ for 2 seconds. The welding effect, spatter, and appearance of the board surface after soldering were observed using an optical microscope.

[0034] 2. Spread rate test: Refer to standard JIS Z 3197 8.3.1.1, use Sn-0.7Cu lead-free solder, and test in a tin bath at 265℃.

[0035] 3. Post-soldering residue: Visually inspect the degree of residue on the copper sheet surface. Scoring criteria: Grade A - Copper sheet surface is dry and clean, with no visible residue; Grade B - Copper sheet surface is basically dry, with slight residue; Grade C - Copper sheet surface has obvious residue or stickiness.

[0036] 4. Copper plate corrosion test: Refer to IPC-TM-650 2.6.15 and test for 240 hours at 40℃ / 93%RH.

[0037] 5. Surface Insulation Resistance (SIR) Test: Refer to IPC-TM-650 2.6.3.7, use IPC-B-24 comb electrode plate, and test for 168 hours under the conditions of 40℃ / 90%RH and 12.5V DC bias.

[0038] The test results are shown in Table 1.

[0039] Table 1. Summary of Performance Tests for Water-Based Fluxes

[0040] The test results in Table 1 show that: (1) Solder joint gloss: Through simulated soldering, the fluxes in Examples 1-5 all showed good tinning properties after soldering, and the solder surface was bright and smooth, without pinholes, and highly glossy. This proves the effectiveness of adding ester additives to the flux in improving the gloss of the solder surface.

[0041] (2) Splatter suppression effect: The fluxes in Examples 1-5 all exhibited low spatter, indicating a significant spatter suppression effect. This is attributed to the regulation of the water evaporation rate by the intermolecular interaction network formed by the ester compound and polyethylene glycol, as well as the synergistic effect of the high-boiling-point solvent.

[0042] (3) Welding activity: The flux spread rate of Examples 1 to 5 was between 75% and 77%, indicating that excellent welding activity was achieved by combining appropriate organic acids and the synergistic wetting effect of ester compounds.

[0043] (4) Reliability and environmental friendliness: Observation showed that the fluxes in Examples 1 to 5 all exhibited a small amount of residue on the surface after soldering. The residue was stable and did not change color. Furthermore, it did not corrode under prolonged humid and hot conditions. The surface insulation resistance test showed that the insulation resistance remained at 10 after the test. 8 Above Ω, no corrosion was observed. This further confirms that the flux of the present invention provides excellent protection for the copper sheet while ensuring welding performance.

[0044] In summary, the low-spatter, high-brightness water-based flux for photovoltaic module welding prepared by this invention exhibits excellent performance in terms of spatter rate, solder joint gloss, welding activity, and reliability, achieving a balance between low spatter and high brightness. It is suitable for high-speed tinning production of photovoltaic module welding strips and module stringing processes.

[0045] The above embodiments are only some preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Embodiments obtained by those skilled in the art through equivalent substitutions or modifications based on the technical solutions and inventive concepts of the present invention within the scope defined by the claims should all be covered within the scope of protection of the present invention.

Claims

1. A low-splatter, high-brightness water-based flux for welding photovoltaic modules, characterized in that, It consists of the following raw materials by weight percentage: Film-forming agent 1-3%, complex organic acid surfactant 2-5%, ester auxiliaries 1-3%, surfactant 0.1-0.5%, high boiling point solvent 3-8%, corrosion inhibitor 0.1-0.5%, antioxidant 0.3-0.5%, and the remaining solvent is deionized water.

2. The low-spatter, high-brightness water-based flux for photovoltaic module welding according to claim 1, characterized in that, The film-forming agent is polyethylene glycol with a molecular weight of 400-6000.

3. The low-spatter, high-brightness water-based flux for photovoltaic module welding according to claim 1, characterized in that, The composite organic acid activator is composed of low-boiling-point organic acid and high-boiling-point organic acid in a mass ratio of 1:0.5 to 1:1.5; the low-boiling-point organic acid is one of malonic acid, glycolic acid, and succinic acid, and the high-boiling-point organic acid is one of glutaric acid, itaconic acid, malic acid, and citric acid.

4. The low-spatter, high-brightness water-based flux for photovoltaic module welding according to claim 1, characterized in that, The ester auxiliaries are one or more of diester esters and polyol esters.

5. The low-spatter, high-brightness water-based flux for photovoltaic module welding according to claim 4, characterized in that, The ester additives are one or more of diethylene glycol diacetate, dimethyl glutarate, dimethyl adipate, polyethylene glycol laurate, propylene glycol methyl ether acetate, and propylene glycol diacetate.

6. The low-spatter, high-brightness water-based flux for photovoltaic module welding according to claim 1, characterized in that, The surfactant is one or more of the following: polyoxyethylene sorbitan monolaurate, fatty alcohol polyoxyethylene ether, isotridecyl alcohol polyoxyethylene ether phosphate, alkylphenol polyoxyethylene polyoxypropylene ether, and octylphenol polyoxyethylene ether.

7. The low-spatter, high-brightness water-based flux for photovoltaic module welding according to claim 1, characterized in that, The high-boiling-point solvent is one or more of tetrahydrofurfuryl alcohol, isopropanol, triethylene glycol butyl ether, dipropylene glycol butyl ether, diethylene glycol butyl ether, dipropylene glycol dimethyl ether, and propylene glycol butyl ether.

8. The low-spatter, high-brightness water-based flux for welding photovoltaic modules according to claim 1, characterized in that, The corrosion inhibitor is one or more of the following: triethanolamine, N,N-methylenebisbenzamide, benzotriazole, methylbenzotriazole, 2-ethylimidazole, dimethylethanolamine, and sodium gluconate.

9. The low-splatter, high-brightness water-based flux for photovoltaic module welding according to claim 1, characterized in that, The antioxidant is one or more of hydroquinone, catechol, tea polyphenols, and 2,6-di-tert-butyl-p-cresol.

10. The method for preparing the low-spatter, high-brightness water-based flux for photovoltaic module welding as described in any one of claims 1 to 9, characterized in that, Includes the following steps: (1) Add deionized water, additives and surfactants to the reaction vessel in sequence, stir evenly to form composite solvent A; (2) Under stirring conditions of 300 to 600 r / min, the high-boiling-point solvent and film-forming agent are added to solvent A, and stirring is continued until the mixture is completely homogeneous to obtain mixture B; (3) Keep stirring, and finally add the compounded organic acid surfactant, corrosion inhibitor and antioxidant to the mixture B, and continue stirring for 20~30 min until the system is completely transparent and uniform; (4) After the obtained solution is allowed to stand, it is filtered through a 0.45-1.0 μm filter membrane to obtain the low-splash, high-brightness water-based flux for welding photovoltaic modules.